Ambivalence and Interpersonal Liking: The Expression of Ambivalence as Social Validation of Attitudinal Conflict - Toribio-Flórez, Daniel; van Harreveld, Frenk; Schneider, Iris K. (Frontiers in Psychology, 2020)
Literature on attitude similarity suggests that sharing similar attitudes enhances interpersonal liking, but it remains unanswered whether this effect also holds for ambivalent attitudes. In the present research, we shed light on the role attitudinal ambivalence plays in interpersonal liking. Specifically, we examine whether people express ambivalence strategically to generate a positive or negative social image, and whether this is dependent on the attitudinal ambivalence of their perceiver. We test two alternative hypotheses. In line with the attitude-similarity effect, people should express ambivalence towards ambivalent others to enhance interpersonal liking, as sharing ambivalence might socially validate the latter’s experience of attitudinal conflict. On the other hand, people might express more univalence, as ambivalence may drive ambivalent others towards the resolution of their attitudinal conflict and univalent stances could help to achieve that goal. In two studies (N = 449, 149), people expressed similar attitudes to those of their perceivers, even when the latter experienced attitudinal conflict (Study 1 and 2). Moreover, they composed an essay, the message of which validated their perceiver’s attitudinal conflict (Study 2). In line with these results, we further observe that the more people experienced their ambivalence as conflicting, the more they liked others who similarly experienced attitudinal conflict (Study 1). These findings suggest that the expression of ambivalence can have important interpersonal functions, as it might lead to an enhanced social image when interacting with those coping with attitudinal conflict.